CuO and CeO2 co-doped catalytic nanomaterial synthesized from red mud and rice husk ash for the deep oxidation of benzene, toluene and xylene - Thanh Tinh, Nguyen; Thi Thuy Van, Nguyen; Phung Anh, Nguyen; Ky Phuong Ha, Huynh; Tri, Nguyen (International Journal of Engineering and Technology, 2018)
CuO-CeO2 catalysts with fixed content supported on material (ZRM) synthesized from red mud and rice husk ash were prepared by wet-ness co-impregnation and conbustion method. The effects of calcination conditions on physic-chemical properties and catalytic performance of CuCe/ZRM catalysts were emphasized. Several techniques, including Brunauer-Emmett-Teller nitrogen physisorption measurements (BET), X-ray powder diffraction (XRD), hydrogen temperature programmed reduction (H2-TPR), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were used to investigate the properties of catalysts. It was obvious that the modification CuO-doped ZRM materials by CeO2 resulted in better surface morphology and more homogenous particles. The results evidenced that calcination conditions strongly affected the particle size, morphology and reduction of CuCe/ZRM catalysts. CuCe/ZRM sample calcined at 500 for 3 hours with higher porous and smaller nanoparticles with higher reduction was the best in terms of activity in deep oxidation of p-xylene at temperature of 275 âˆ’ 400Â°C, achieving a 90% p-xylene conversion at 350 oC with WHSV of 12,000mL.h-1.g-1. The catalytic activity of the most prominent catalyst (CuCe/ZRM-500-3) sample increased in the following order: benzene < toluene < p-xylene. The presence of water vapor had a negative effect on catalytic activity due to the competition of water molecules with VOCs molecules for adsorption on surface active sites.Â